SIMPLE MEDICAL VENTILATOR DESIGN WITH MICROCONTROLLER-BASED O2 INPUT - Daffa Ammarandika; Rafiudin Syam; Pitoyo Yuliatmojo (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2024)
This research aims to help treat patients experiencing respiratory disorders, one of which is for Covid-19 patients. The design of this tool regulates the entry and exit of oxygen based on solenoid valve control with an Arduino Mega 2560 microcontroller. This tool is also equipped with several components, namely, the MAX30100 Sensor to detect the patient's heart rate and oxygen saturation, a Thermocouple Sensor with a MAX6675 Module to detect the oxygen temperature which will be displayed on the 20x4 LCD (Liquid Crystal Display) and a Heater as an oxygen heater on this tool. The method used in this research is the engineering system method. The results of the study show that the system created is capable of blowing oxygen 14 times per minute with an oxygen volume of 500 ml at a time. In addition, this tool displays data on the patient's oxygen temperature, heart rate and oxygen saturation on the LCD. The performance of the MAX30100 Sensor can detect the patient's heart rate and oxygen saturation with an error percentage of 0.009% and 0.547%. Thermocouple sensors A and B have successfully measured oxygen temperature quite accurately with an average error percentage of 0.010% and 0.030%.